QUALITY CONTROL, SAFETY OF RAW MEAT AND TURKEY MEAT PATE AND JUSTIFICATION OF RECIPES AND STERILIZATION REGIMENS - Prylipko, Tetiana (Podilian Bulletin: Agriculture, Engineering, Economics, 2019)
In the study of the toxicity of turkey meat, it was found that the content of toxic elements in the tested batches did not exceed the permitted levels. Thus, the lead content in meat was 0.08 mg / kg, which is 6.2 times (P <0.05) less than the determined norm, the arsenic content was at the level of 0.02 mg / kg or 5 times (P <0.05) is less than the standard, and cadmium and mercury are not detected at all. Based on the defined function and constraints, we create a spreadsheet in MS Excel according to functional dependency. The built-in Excel Solution Finder was used to determine the optimum composition of components. The purpose of optimizing the recipe composition of the original products is its balance in basic nutrients, the maximum approximation to the following requirements of healthy nutrition is observed at the ratio of proteins: fats: carbohydrates - 1: 1,3: 4; essential amino acids lysine: tryptophan: methionine - 1: 3: 3; fatty acid composition of polyunsaturated: saturated: monounsaturated - 1: 3: 6; Omega 6: Omega 3 - 10: 1; the ratio of trace elements: Ca: Mg = 1: 1,5; Ca: P = 1: 0.6. The highest percentage (31%) of canned pate is made from turkey meat, namely turkey meat. The specified meat raw material has undergone laboratory testing and meets the requirements of quality and safety regulations. Beef liver is included in the recipe in the amount of 10% of the total mass of raw materials and at its nutritional value complements the quality indicators of pate. In order to give a gentle texture to the pate, a fermented pork skin in the brine is put into the recipe. The indices of mass fraction of moisture of rock were 66.8% (P <0.01), fat - 20.0% (P <0.01), protein - 8.2% (P <0.01), ashes - 1.46% (P <0.01), carbohydrates - 3.5% (P <0.01) and are within the limits specified by the regulatory documentation. The caloric content of the meat pate is low and is only 226.8 kcal. The results of studies of turkey meat pate showed that the mass concentration of toxic elements meets regulatory standards, in particular the lead content was 0.02 mg / kg (P <0.03) or 30 times less than the allowable level, cadmium - 0.01 mg / kg (P <0.01) or 30 times less, arsenic - 0.05 mg / kg (P <0.01) or 20 times less, mercury - 0.005 mg / kg ( P <0.01) or 20 times less. Indicators of organochlorine pesticide content were in particular the gamma isomer of HCG - 0.04 mg / kg (P <0.01) or 2.5 times less than normal, DDT and its metabolites - 0.03 mg / kg (P <0.05) or 3.3 times less